Acute Limb Ischemia due to Arterial Thrombosis in a Patient with COVID-19 Pneumonia: A Case Report - Renata Primasari; Yetti Hernaningsih; Hartono Kahar; Bramantono Bramantono (Interna Publishing, 2022)
The COVID-19 pandemic has caused more than 4 million deaths worldwide to date. During the course of the COVID-19 pandemic, thrombotic complications due to hypercoagulable state have emerged as an important issue. Acute limb ischemia is one of emergency cases in vascular disease caused by a sudden decrease in arterial limbs perfusion. Here, we report a 53-year-old male patient with severe COVID-19 and a history of uncontrolled type 2 diabetes mellitus (T2DM) who developed extensive arterial thrombosis and limb ischemia despite being on therapeutic-dose anticoagulation, requiring surgical intervention. Right and left leg open thrombectomy was performed at day 7 after admission due to the excruciating pain and the worsening of the limb conditions. The patient was transferred to intensive care unit in emergency room because of the unstable hemodynamic and passed away a few hours after the surgery. For critically ill patients with COVID-19, special attention should be paid to abnormal coagulation dysfunction and microcirculatory disorders.